Małżeństwo w "Konstytucjach Apostolskich" - Strękowski, Stanisław (Vox Patrum, 2025)
The Apocrypha, known as the Apostolic Constitutions, is a collection of Church laws that was created around 375-380, most likely in Antioch in a Judeo-Christian environment. It is an extensive compilation consisting of many earlier Church documents, addressing various issues that concerned Christians in the first centuries. This document also included a few but important for Christians content regarding marriage, its indissolubility, its relationship to virginity, clerical marriages, virgins and widows. All the ordinances regarding this issue generally reflect the views of the Church Fathers in the East in the 4th century. This article presents the regulations regarding the institution of marriage in the context of other church documents and the views of authors from the 4th century. Although this is an apocryphal work, the content provided by the compiler of the Apostolic Constitutions on the issue of marriage does not differ substantially from the widespread views and practices in the Eastern Church.